Endocrinology of parturition - Norwitz, Errol (Henry Stewart Talks, 2007)
Parturition, Molecular mechanisms of labor, both at term and preterm, Preterm labor, Risk factors for preterm birth, Genetics of preterm birth, Prediction and prevention of preterm birth, Treatment of preterm labor, Post-term pregnancy
Reviewed at 2019/12/04